Pengaruh Store Atmosphere Terhadap Keputusan Pembelian Konsumen Pada Next Salon For Men Jalan DR. Mansyur. No. 94 Medan. - Frans Kristanto (Jurnal Niaga & Bisnis (e-journal), 2015)
This research aimstoanalyze theatmosphereinthe NextstoreSalonFor Men, analyzingconsumerpurchasing decisionsat NextSalonfor Men, andanalyze the effectof storeatmosphereon consumer purchasing decisions. Forms of assosiative method used in this study with quantitative approach with view to find how much influence between variable X store atmosphere of the variable Y is consumer purchase decision.  From the calculation of simple linear regression, obtained Y = 7.148 + 0.605x constant means if the store atmosphere, then there will be 7.148 of the consumer purchase decisions and store atmosphere when raised 100% the consumer purchase decisions will increase by 0.605. Obtained from t test t price 13.137 > t table t price1.993 that shows the significant influence on consumer purchase decisions  Next Salon For Men Jalan. Dr. Mansyur number 94 Medan. Great influence of store atmosphere on consumer purchase decisions used formula coffiecient of determination obtained results of 70.6%. That is accomplished consumer purchase decision are influenced by store atmosphere of 70.6%. Keywords : Store Atmosphere, Consumer Purchase Decisions.